KESESUAIAN LAHAN DAN EVALUASI RUMUS BRAAK UNTUK PENGEMBANGAN TANAMAN KENTANG DI KAKI BUKIT KABA BENGKULU - Priyono Prawito; Eka Susiani (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
In order to get optimal growth and production, potato (Solanum tuberosum) should be cultivated on suitable land. Principally, land suitability evaluation is fitting land quality with plant growth requirement. The purposesof this study were: (1) to evaluate land suitability for potato cultivation in Bukit Kaba Foot Slope Bengkulu (BKFSB), and (2) to determine the air temperature gradient for Braak equation in calculating air temperature. Landsuitability evaluation has been conducted by overlying the land characteristic map with the potato growth requirement, to produce land suitability classes with various restriction factors. Temperature gradient was calculated by plotting elevation and air temperature data from 3 weather stations into the Braak equation. Land suitability evaluation with area study of 48.410 ha showed that actual area S (marginally suitable with restriction factor of air temperature 20-23 oC) is 5,150.00 ha (10.63%); S 3ts 3t (marginally suitable with restriction factor of air temperature 20-23 oC and slope of 8-15%) is 1.727,50 ha (3.56%); N (not suitable at present with restriction factor of slope 15-25%) is 2,250.00 ha (4.67%); and N2 1s (permanently not suitable with restriction factor of air temperature >23 oC, slope >25%, and protected forest) is 39.282,50 ha (81.14%). The potential area S is 9,127.50 ha (18.86%) and N2 3t  is 39,282.50 ha (81.14%). To extend potato cultivation area in BKFB, new potato cultivars suitable for this area should be selected, and enhancing cultivation system with terrasering especially in slopping land as well ascontour planting should be done. The air temperature gradient in BKFSB area was 0.29 C each 100 m-elevation increase from sea level (0.29 oC hm-1).